Tratamento da tuberculose na Atenção Básica: avaliação de estrutura e processo dos serviços de saúde - Silva, Daiane Medeiros da (2013)
The study had as objective to evaluate the structure and the service process of Basic Attention (BA) for the treatment of tuberculosis in a port city of Paraíba. This is an epidemiological study, descriptive, of inquiry type, of quantitative approach, which adopted as methodological axis the components of evaluation of health services, structure and process. Participated in the study 117 professionals in 18 Family Health Units of the city, interviewed by means of a structured instrument, elaborated, adapted, and validated by the Operating Study Group in Tuberculosis of the Brazilian Network of Research in Tuberculosis, containing indicators of performance evaluations of health professionals in monitoring cases of TB in the context of Primary health Attention. Data analysis was carried out through the distribution of absolute/relative frequency and the construction of indicators, using proportions, to classify the performance of variables, in order to evaluate which variable would be interfering in the negative evaluation of services, and through averages and confidence intervals for the classification of health services. Regarding the component structure, human resource item, the involvement of staff or other health professionals in the treatment of sick people with TB showed to be unsatisfactory, as well as the realization of training, both Tuberculosis Control Program of the city as by the health services, for minimal service staff. Regarding the item physical resources, the availability of transportation tickets achieved a critical performance, differing from the basic food basket that showed to be unsatisfactory. The availability of supplies/equipment by health units for TB control and medicines for TB showed satisfactory performance. Regarding the item service organization, the conduction of discussions of tuberculosis cases between health professionals showed unsatisfactory performance. Both access to the consultation within 24 hours, as well as the guidance for TB patients in relation for the search for attendance out of the date set if they need, showed satisfactory performance. The attendance for the demand of TB services by laboratories proved critical, this classification is achieved by variables relating to the access to the test result sputum bacilloscopy in seven days and the existence computerized system containing information about the TB patient. The articulation of health services of TB with other levels showed unsatisfactory performance. With regard to the component process, the joint discussion with the patient as the way of realization of their accompaniment obtained unsatisfactory performance, since the offer of Directly Observed Treatment at home was classified as satisfactory. The minimum realization of bimonthly sputum bacilloscopy for the control of TB treatment obtained unsatisfactory result. The counter-reference of information achieved critical performance. In the classification of services, only health service C achieved satisfactory performance, averaging 84,2 and IC= [63.1; 105,0]. Through these results, it is notes deficiencies in both organization of health services and in the process of the work of professionals, which are guided on the curative model, elucidating the fragmented character of control actions of TB and recognizing only the biological and the healing as object of study.